pH metric investigation on speciation studies of 5-Sulfosalicylic acid complexes of Co(II), Ni(II) and Cu(II) in DMF-water mixtures - Balakrishna, M. (2019)
Speciation of Co(II), Ni(II) and Cu(II) complexes with 5-Sulfosalicylic acid (5-SSA) in the presence of N, N’- Dimethyl formamide-water mixtures(0.0-60% v/v) at an ionic strength of 0.16 mol dm-3 and temperature 303 K were investigated pH metrically. The existence of different binary complex species was established from modeling studies using the computer program MINIQUAD75. The increased stability of the complexes with increasing DMF was explained by electrostatic forces. The influence of the DMF on the chemical speciation is discussed based on the dielectric constant of the medium. Distribution diagrams of various species of the complexes in relation to pH are presented.